Inhaled GM-CSF in a Pulmonary Alveolar Proteinosis Patient Refractory to Plasmapheresis Combined with Multiple Whole Lung Lavages - Francesca Mariani; Elena Paracchini; Davide Piloni; Zamir Kadija; Elena Salvaterra; Laura Divizia; Giuseppe Rodi; Carmine Tinelli; Federica Meloni; Ilaria Campo (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
A  autoimmune  Pulmonary  Alveolar  Proteinosis  (PAP)  patient  with  persistent  disease  underwent  3 Whole Lung Lavages (WLLs), 10 plasmapheresis sessions and further 3 WLL, from October 2004 to May 2007. Nevertheless HRTC and pulmonary function test (PFT) showed a persistent residual disease of mild degree. At the beginning of 2010, the patient was admitted to inhaled rGM-CSF (Sargramostim) therapy as compassionate treatment. GM-CSF was administered by Akita 2 nebulizer (Vectura), as follow: 250 mcg/day every other week for 12 weeks, then 250 mcg/day on 2 consecutive days every 2 weeks for 6 months. Follow up visits were scheduled at 3, 10, 18, 30 months and after that once a year. Functional and HRCT data and PaO2 were collected. Since the start of the inhaled GM-CSF therapy, the patient no more required WLL. Furthermore we found a significant increase in DLCO% (p=0.013) and FVC% (p=0.023) while %FEV1 show  a  positive  trend. No  substantial  differences  in  blood  gas  analysis. The  pulmonary  involvement  at HRCT shows a significant decrease of lung infiltrates (p=0.039) in terms of pathological segments. These data underscore the utility of inhaled GM-CSF not only in case of progressing disease but also in case of refractory patients with persistent lung infiltrates, in order to increase the response rate.